Replacement of Serine363and Serine375Codons by Alanine in Ratμ-Opioid ReceptorcDNA: Replacement of serine363and serine375by alanine in μ-receptor - Rabbani, Mohammad; Mir Mohammad Sadeghi, Hamid; Omidsalary, Ali; Langari, Jahangir; Moazen, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2007)
The aim of this study was to use site directed mutagenesis technique to constructa vector in which serine363and serine375residues of the COOH-terminal portion ofthe μ-opioid receptor (MOR) were substituted by alanine. These constructs areessential in studying G-protein coupled receptor kinase-mediated MOR desensiti-zation. The nested PCR carried out for conversion of serine363and serine375to alanineresulted in the production of a band comparable to the expected size of 1400 bp.Restriction analysis of these bands confirmed the integrity of the PCR products.Ligation of the mutated PCR product into pcDNA3 and its digestion with appropriaterestriction enzymes further confirmed the integrity of the PCR product and itsorientation into the vector.